Návrh elektrochemického senzoru pro měření ethanolu - Božek, Jakub (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2023)
Tato bakalářská práce se zabývá problematikou tištěných elektrochemických senzorů a měřením glukózy a ethanolu v roztoku krve. V teoretické části je popsána problematika senzorů, jejich rozdělení a využití. Dále se práce detailněji zaměřuje na elektrochemické senzory, měření a jejich elektrody. V praktické části jsou potom zhotoveny návrhy senzorů, zhotovení senzorů a provedené měření.

This bachelor thesis deals with printed electrochemical sensors and the measurement of glucose and ethanol in blood solution. The theoretical part describes the sensors, their distribution and applications. Then the thesis focuses in detail on electrochemical sensors, measurements and their electrodes. Then, in the practical part, the sensor designs, fabrication of the sensors and the measurements made are presented.
Design of an electrochemical sensor for ethanol measurement
Keywords: Senzory; Elektrochemické senzory; Tlustovrstvá technologie; Voltametrie; tištěné elektrody; Sensors; Electrochemical sensors; Thick film technology; Voltammetry; Printed electrodes